REKONSTUKSI PERAN NEGARA DALAM PENYELENGGARAAN NEGARA SECARA KONSTITUSIONAL - Lukman Hakim (Faculty of Law, Universitas Diponegoro, 2011)
Actually in the system of state structure, there are some theoretical thoughs concerning with the need for a country to play a role as the regulator for the citizens' protection. There is a thought starting from the historical course of a country to become a social system that should protect its citizens and give an assurance for its prosperity. When the existence of a country is from an interactional process producing a commitment to build an order and peace, therefore there is an idea to create an organisation that may accommodate all intentions and interests of the citizens. Kata kunci: Peran Negara, Fungsi Negara, Lembaga Negara.